1992
DOI: 10.1055/s-0038-1656346
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Binding Heterogeneity of Lp(a): Consequences for Fibrin Binding and Inhibition of Plasminogen Activation

Abstract: SummaryLipoprotein(a) [Lp(a)] is recognized as an independent risk factor for atherosclerosis. Lp(a) consists of a LDL-like moiety with an additional glycoprotein, apo(a), linked to apolipoprotein B-100. Apo(a) has a high homology with plasminogen (Pg). In vivo, Pg is activated on a fibrin surface by tissue Pg activator (tPA). We prepared Lp(a) from plasma by sequential ultracentrifugation followed by lysine-sepharose affinity chromatography. We found that a changing (donor dependent) fraction of the Lp(a) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…This group has also provided the cogent warning that one cannot presume that measurement of lysine binding of Lp(a) variants will faithfully translate to relative binding affinity of Lp(a) to fibrin itself (36, 47). Leerink and colleagues isolated lysine binding and nonbinding Lp(a) fractions from several human donors (14). Although the molecular causes of this binding difference were not determined, they reported that the lysine binding fraction of Lp(a) bound fibrin and inhibited plasminogen activation, whereas the lysine nonbinding fraction did neither (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This group has also provided the cogent warning that one cannot presume that measurement of lysine binding of Lp(a) variants will faithfully translate to relative binding affinity of Lp(a) to fibrin itself (36, 47). Leerink and colleagues isolated lysine binding and nonbinding Lp(a) fractions from several human donors (14). Although the molecular causes of this binding difference were not determined, they reported that the lysine binding fraction of Lp(a) bound fibrin and inhibited plasminogen activation, whereas the lysine nonbinding fraction did neither (14).…”
Section: Discussionmentioning
confidence: 99%
“…Leerink and colleagues isolated lysine binding and nonbinding Lp(a) fractions from several human donors (14). Although the molecular causes of this binding difference were not determined, they reported that the lysine binding fraction of Lp(a) bound fibrin and inhibited plasminogen activation, whereas the lysine nonbinding fraction did neither (14). Since it is not yet practical to conduct human clinical trials with naturally occurring sequence variants that are of a scope to achieve statistically significant conclusions, we have used a transgenic mouse model of fatty streak development to address the in vivo effect of the LBS of apo(a) kringle 4-37.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pepin et al [8] found that Lp(a) in atherosclerotic lesions was oxidized, and the oxidized Lp(a) could be a more tightly bound fraction than apoB. Two studies reported large variations in the lysine binding capacity of Lp(a) purified from different individuals [26,27]. This heterogeneity appeared not to be associated with apo(a) isoforms.…”
Section: Lp(a) and Fibrinolysismentioning
confidence: 99%